Pelatihan dan Pendampingan Proses Pembuatan Punch and Dies dengan Menggunakan Material SKD 11 pada UMKM di CV. Gama Satya Engineering - Amir Amir; Aris Munandar; Nurhalim Nurhalim; Ahmad Solihin; Agus Budiyanto; Muchammad Chusnan Aprianto (Lembaga Pengembangan Kinerja Dosen, 2025)
The manufacturing process of dies and punches requires high precision to produce components that are exactly in accordance with the given design specifications. Every step in the manufacture of dies and punches must be carried out carefully to ensure that the final result meets the quality and safety standards required in the industry. The manufacture of dies requires extra precision. These are not just molds, but tools that are capable of providing consistent shape and precision in every molding operation. Punches, an equally important counterpart, are designed to fit dies and provide clean and precise cuts on the processed material. This process not only produces tools but also demonstrates a dedication to technical excellence and precision. Every step is taken diligently, from initial conception to implementation on the production line. In the world of manufacturing, dies and punches are about transforming ideas into solid reality, playing a crucial role in supporting the advancement of modern industry.